Dermoid cyst of testis in a 72-year-old man: A rare entity - Babu Kinnera Vijay; Mandyam Kumaraswamy; Yootla Mutheeswaraiah; Vutukuru Venkatarami (Urology Annals, 2009)
Dermoid cyst is a mature-type teratoma containing sebaceous material and predominantly tufts of hair or teeth along with skin appendages. It is most commonly observed in the ovary but is rare in the testis, and only a few cases have been reported so far. In most of the reports, the cyst tended to be diagnosed in a younger age group. Here, we report a dermoid cyst of the testis in a 72-year-old man.